The Determinants of Econometric Society Fellows Elections - Hamermesh, Daniel S.; Schmidt, Peter (Econometrica, 2003)
We study the results of elections of Fellows of the Econometric Society. We aremotivated largely by the question of whether these elections are “fair,” where our deﬁni-tion of fairness is that votes are based solely on the quality of the candidates. If so, thenconditional on quality other characteristics of the candidates (such as geographic locationor subspecialty) should not inﬂuence the probability of election. We ﬁnd that, conditionalon a number of measures of the quality of the candidates, other characteristics do sig-niﬁcantly predict election. For example, an Australian econometrician is less likely to beelected than a North America-based economic theorist. This is true whether or not wecontrol for quality measures.One might object that even fully informed individuals may differ in their assessment ofquality, and that neither the voters nor the authors of this study are fully informed aboutcandidates’ quality. This is true in any study of the impact of ascriptive characteristics onoutcomes. We discuss various interpretations of our ﬁndings in the conclusion, but readersmust draw their own conclusions about what the results imply about the roles of qualityand fairness in this electoral process.1 the electoral institutionMost members of the economics profession consider election as a Fellow as an honor.It recognizes prior professional achievements (within what are the more technical areasof economics). There are roughly 500 living Fellows. Names are placed on the ballot inone of two ways: (i) by the Nominating Committee of the Society, or (ii) by petition ofat least three members (who need not be but usually are current Fellows). The ballotcontains the candidate’s name and current afﬁliation; a list of at most six publications; ashort statement of the candidate’s contribution to economics; and an indication of whetherthe nomination was by Committee or by endorsers and, if the latter (from 1990 through2000), the names of all the endorsers. The ballot deadline is April 30.The electorate, dues-paying current Fellows, receive the ballot in early autumn alongwith the nomination form for each candidate, mark their ballots, and return them tothe Society’s ofﬁce. Results are announced in December. Names on the ballot are inalphabetical order, with a different starting point in each annual election. Voters checkthe names of individuals whom they wish to be elected. A candidate is elected who isapproved on at least 30 percent of the ballots returned. (Typically about half the eligibleFellows cast votes.) Losing candidates can be nominated in later years by either of thetwo methods, but the process must be undertaken de novo.